Negative emissions—Part 2: Costs, potentials and side effects. (22nd May 2018) - Fuss, Sabine; Lamb, William F; Callaghan, Max W; Hilaire, Jérôme; Creutzig, Felix; Amann, Thorben; Beringer, Tim; de Oliveira Garcia, Wagner; Hartmann, Jens; Khanna, Tarun; Luderer, Gunnar; Nemet, Gregory F; et al.
Abstract: The most recent IPCC assessment has shown an important role for negative emissions technologies (NETs) in limiting global warming to 2 °C cost-effectively. However, a bottom-up, systematic, reproducible, and transparent literature assessment of the different options to remove CO2 from the atmosphere is currently missing. In part 1 of this three-part review on NETs, we assemble a comprehensive set of the relevant literature so far published, focusing on seven technologies: bioenergy with carbon capture and storage (BECCS), afforestation and reforestation, direct air carbon capture and storage (DACCS), enhanced weathering, ocean fertilisation, biochar, and soil carbon sequestration. In this part, part 2 of the review, we present estimates of costs, potentials, and side-effects for these technologies, and qualify them with the authors' assessment. Part 3 reviews the innovation and scaling challenges that must be addressed to realise NETs deployment as a viable climate mitigation strategy. Based on a systematic review of the literature, our best estimates for sustainable global NET potentials in 2050 are 0.5–3.6 GtCO2 yr −1 for afforestation and reforestation, 0.5–5 GtCO2 yr −1 for BECCS, 0.5–2 GtCO2 yr −1 for biochar, 2–4 GtCO2 yr −1 for enhanced weathering, 0.5–5 GtCO2 yr −1 for DACCS, and up to 5 GtCO2 yr −1 for soil carbon sequestration. Costs vary widely across the technologies, as do their permanency and cumulative potentials beyond 2050. It is unlikely that a single NET will be able to sustainably meet the rates of carbon uptake described in integrated assessment pathways consistent with 1.5 °C of global warming.